STUDI PENENTUAN PEGAWAI BERPRESTASI DENGAN METODE WEIGHTED PRODUCT (WP) DALAM MENINGKATKAN KINERJA SEKRETARIAT DAERAH KOTA METRO - Gunawan Gunawan (Universitas Muhammadiyah Metro, 2020)
This study aims to determine what criteria can be used to determine high-performing employees and also find out methods that can be used to determine high-achieving employees. The problem is whether Employee Work Targets (targets and achievements) and Work Behavior (service orientation, integrity, commitment, discipline, cooperation and leadership) can be used as criteria in determining employee performance and whether the Weighted Product (WP) method can be used as a method of analysis in determining employee achievement. This study is a study that seeks to determine employee achievement using the Weighted Product (WP) method by using SKP (Employee Work Goals) and Work Behavior as assessed criteria. The population in this study are employees of the Metro City Regional Secretariat office with random sampling. To determine the number of samples a cluster or group system is used proportionally where a large number of population groups are also sampled and vice versa. Based on the analysis using the method of Weighted Product (WP) shows that the employee with the highest vector V value is considered the best / highest performing employee. By using this method the determination of outstanding employees can be done in an objective, measurable, accountable and transparent.